A novel human anti‐AXL monoclonal antibody attenuates tumour cell migration. (7th June 2019) - Duan, Yanting; Luo, Longlong; Qiao, Chunxia; Li, Xinying; Wang, Jing; Liu, Hao; Zhou, Tingting; Shen, Beifen; Lv, Ming; Feng, Jiannan
Abstract: TAM family members (TYRO3, AXL and MERTK) play essential roles in the resolution of inflammation and in infectious diseases and cancer. AXL, a tyrosine kinase receptor, is commonly overexpressed in several solid tumours and numerous hematopoietic malignancies including acute myeloid leukaemia, acute lymphocytic leukaemia, chronic myeloid leukaemia, chronic lymphocytic leukaemia and multiple myeloma. AXL significantly promotes tumour cell migration, invasion and metastasis, as well as angiogenesis. AXL also plays an important role in inflammation and macrophage ontogeny. Recent studies have revealed that AXL contributes to leukaemic phenotypes through activation of oncogenic signalling pathways that lead to increased cell migration and proliferation. To evaluate the mechanisms underlying the role of AXL signalling in tumour metastasis, we screened a phage display library to generate a novel human monoclonal antibody, named DAXL‐88, that recognizes both human and murine AXL. The concentrations of DAXL‐88 required for 50% maximal binding to human and murine AXL were 0.118 and 0.164 μg/mL, respectively. Furthermore, DAXL‐88 bound to human AXL with high affinity ( K D  ~ 370 pM). DAXL‐88 blocked the interaction between AXL and its ligand, growth arrest‐specific gene 6 (GAS6), with a half maximal inhibitory concentration of 2.16 μg/mL. Moreover, DAXL‐88 inhibited AXL/GAS6‐dependent cell signalling, which is implicated in cell migration and invasion. In conclusion, the novel anti‐AXL DAXL‐88 high‐affinity antibody blocks the interaction between AXL and GAS6 and inhibits tumour cell migration and invasion induced by GAS6. Thus, DAXL‐88 offers promise for the development of targeted therapeutic strategies in solid tumours, leukaemias and other lymphoid neoplasms.